Palmitate and Nitric Oxide Regulate the Expression of Spexin and Galanin Receptors 2 and 3 in Hypothalamic Neurons. (1st November 2020) - Tran, Andy; Loganathan, Neruja; McIlwraith, Emma K.; Belsham, Denise D.
Graphical abstract: Highlights: Novel anorexigenic neuropeptide spexin is upregulated by nitric oxide and palmitate. Receptors for spexin, galanin receptors 2 and 3, are also induced by nitric oxide and palmitate. NO- and palmitate-mediated regulation occurs through a PKC mechanism. Blocking endoplasmic reticulum stress normalizes spexin and galanin receptor mRNA levels. Transcription factor C/EBP-β is induced by nitric oxide and binds to the spexin enhancer. Abstract: Spexin (SPX) is a novel satiety factor that putatively binds the galanin receptors R2 and R3 (GalR2/R3). SPX reduces body weight, and circulating SPX is decreased in obesity. It is unknown how SPX and its receptors are regulated in the hypothalamus, critical for energy homeostasis. We therefore examined the regulation of hypothalamic Spx, GalR2 and GalR3 gene expression in mouse primary and immortalized hypothalamic neurons. We report that Spx, GalR2 and GalR3 mRNA levels were regulated by acute treatments of palmitate, a dietary saturated fatty acid, as well as the nitric oxide (NO) donor sodium nitroprusside (SNP), but through a pathway independent of cyclic GMP and protein kinase G. Additionally, the palmitate- and NO-mediated induction of Spx and galanin receptors was blocked with the PKC inhibitor k252c. Furthermore, palmitate induced mRNA levels of endoplasmic reticulum (ER) stress markers, including Chop, Grp78 and Bax/Bcl2, as well as C/ebp-β, whereas SNP induced Bax/Bcl2 and C/ebp-β . Transcriptional changes in Spx, GalR2, GalR3, C/ebp-β and ER stress marker mRNAs were blocked by pre-treatment with at least one of the chemical chaperones PBA or TUDCA. We also describe the presence of OCT-1 and C/EBP-β response elements in the 5′ regulatory region of Spx and demonstrate that SNP increases binding of C/EBP-β to this region, but not Oct-1 mRNA nor OCT-1 binding. Our findings suggest an acute modulation of anorexigenic SPX signaling by palmitate and NO. Furthermore, ER stress and C/EBP-β appear to mediate the changes in Spx, GalR2 and GalR3 in hypothalamic neurons.